Srpski - Mirković, Nikola; Jovanović, Blagota; Srpski; Srpski; Srpski; Mirković, Anđelka; Simeunović, Zlatko; Žukovski, Dejan (Proceedings, Electrical engineering institute "Nikola Tesla", 2025)
Uninterruptible Power Supply (UPS) systems are of vital importance for many consumers in complex facilities such as a thermal power plant. This paper presents a solution for the parallel operation of two inverters with nominal powers of 60 kVA, based on controlling the nature of the inverters. All challenges and technical details of parallelizing the two inverters are presented, from uniform load sharing and communication to establishing a "master-slave" relationship, and even the transient phenomena during the failure of one of the inverters. Detailed simulations of all relevant events and phenomena are simulated using the Plecs software tool. In accordance with the calculations, the inverters were developed, and experimental results of the operation of these inverters under simulated operational conditions are also included.